Joyful noise - Fleischman, Paul; Beddows, Eric (Harper & Row, Publishers United States, 1988)
A collection of poems describing the characteristics and activities of a variety of insects.
John Newberry Medal
8 - 12 years
Keywords: Insects -- Juvenile poetry; Children's poetry, American; Insects -- Poetry; American Poetry